Genomic footprints of activated telomere maintenance mechanisms in cancer - Sieverling, Lina Katharine; Hong, Chen; Koser, Sandra D.; Ginsbach, Philip; Kleinheinz, Kortine; Hutter, Barbara; Braun, Delia; Cortés-Ciriano, Isidro; Xi, Ruibin; Kabbe, Rolf; Park, Peter J.; Eils, Roland; et al. (Nature Communications, 2020)
In somatic cells the mechanisms maintaining the chromosome ends are normally inactivated; however, cancer cells can re-activate these pathways to support continuous growth. Here, the authors characterize the telomeric landscapes across tumour types and identify genomic alterations associated with different telomere maintenance mechanisms.
Gesehen am 02.04.2020